Survey Perilaku Hidup Bersih dan Sehat (PHBS) Siswa SMP Negeri 1 Pakisjaya Khoirullah - Khoirullah Khoirullah; Setio Nugroho; Rolly Afrinaldi; Deden Akbar Izzuddin (Jurnal Ilmiah Wahana Pendidikan, 2021)
the Clean and Healthy Life Behavior (PHBS) of students of SMPN 1 Pakisjaya? Based on the above problems, the purpose of this study is to determine the Clean and Healthy Life Behavior (PHBS) of students of SMPN 1 Pakisjaya. This study used a survey method with a descriptive quantitative approach. There is a sampling using random sampling technique, with a total sample of 83 students at Pakisjaya State Junior High School. The data collection tool to measure Clean and Healthy Behavior (PHBS) uses a Clean and Healthy Life Behavior Questionnaire (PHBS). From the results of this study, it is known that the Clean and Healthy Behavior of SMP Negeri 1 Pakisjaya students stated that they were in the "very good" category with a percentage of 50.6%, in the "good" category with a percentage of 19. 3%, in the "quite good" category with a percentage of 22.9%, in the "not good" category with a percentage of 0%, and in the "very poor" category with a percentage of 7.2%. So it can be concluded that the Clean and Healthy Behavior of SMP Negeri 1 Pakisjaya students is Very Good